Role of SMC1 in Overcoming Drug Resistance in Triple Negative Breast Cancer - Yadav, Sushma (Public Library of Science, 2013)
Triple-negative breast cancer (TNBC) is one of the hardest subtypes of breast cancer to treat due to the heterogeneity of the disease and absence of well-defined molecular targets. Emerging evidence has shown the role of cohesin in the formation and progression of various cancers including colon and lung cancer but the role of cohesin in breast cancer remains elusive. Our data showed that structural maintenance of chromosome 1 (SMC1), a subunit of the cohesin protein complex, is differentially overexpressed both at RNA and protein level in a panel of TNBC cell lines as compared to normal epithelial or luminal breast cancer cells, suggesting that the amplified product of this normal gene may play role in tumorigenesis in TNBC. In addition, our results show that induced overexpression of SMC1 through transient transfection enhanced cell migration and anchorage independent growth while its suppression with targeted small interfering RNA (siRNA) reduced the migration ability of TNBC cells. Increased expression of SMC1 also lead to increase in the mesenchymal marker vimentin and decrease in the normal epithelial marker, E-cadherin. Immunocytochemical studies along with flow cytometry and cell fractionation showed the localization of SMC1 in the nucleus, cytoplasm and also in the plasma membrane. The knockdown of SMC1 by siRNA sensitized the TNBC cells towards a PARP inhibitor (ABT-888) and IC50 was approximately three fold less than ABT-888 alone. The cytotoxic effect of combination of SMC1 suppression and ABT-888 was also confirmed by the colony propagation assay. Taken together, these studies report for the first time that SMC1 is overexpressed in TNBC cells where it plays a role in cell migration and drug sensitivity, and thus provides a potential therapeutic target for this highly invasive breast cancer subtype.